2021
DOI: 10.1371/journal.pone.0245258
|View full text |Cite
|
Sign up to set email alerts
|

Computational drug repurposing strategy predicted peptide-based drugs that can potentially inhibit the interaction of SARS-CoV-2 spike protein with its target (humanACE2)

Abstract: Drug repurposing for COVID-19 has several potential benefits including shorter development time, reduced costs and regulatory support for faster time to market for treatment that can alleviate the current pandemic. The current study used molecular docking, molecular dynamics and protein-protein interaction simulations to predict drugs from the Drug Bank that can bind to the SARS-CoV-2 spike protein interacting surface on the human angiotensin-converting enzyme 2 (hACE2) receptor. The study predicted a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Similarly, 15 drugs-quinapril, sofosbuvir, amphotericin B, baloxavir marboxil, fosinopril, danoprevir, clarithromycin, atrovastatin, telmisartan, sulfamethoxazole, virginiamycin, micafungin, tunicamycin, caspofungin, and fidaxomicin-which are FDA-approved, were established as SARS-CoV-2 protein inhibitors in an approach confirmed by docking protocol. They could be explored as drug candidates against COVID-19 in the future and be repurposed against SARS-COV-2 [64].…”
Section: Approaches Based On Structurementioning
confidence: 99%
“…Similarly, 15 drugs-quinapril, sofosbuvir, amphotericin B, baloxavir marboxil, fosinopril, danoprevir, clarithromycin, atrovastatin, telmisartan, sulfamethoxazole, virginiamycin, micafungin, tunicamycin, caspofungin, and fidaxomicin-which are FDA-approved, were established as SARS-CoV-2 protein inhibitors in an approach confirmed by docking protocol. They could be explored as drug candidates against COVID-19 in the future and be repurposed against SARS-COV-2 [64].…”
Section: Approaches Based On Structurementioning
confidence: 99%
“…It has been also demonstrated that peptides retrieved from the Antiviral Peptides Database (AVPdb; ( 68)) can interact with several target proteins involved in the SARS-CoV2 virus life cycle like the receptor-binding domain of spike protein and hACE2 receptor (42). Interestingly, two peptides namely Sar9 Met (O2)11-Substance P and Sar9 Met (O2)11-Substance P were able to bind to the hACE2 receptor which modulate the interaction of viral particles with its host cell receptors (47).…”
Section: D Interactions In the Active Site And Ligand Receptor Interactions Distance (å)mentioning
confidence: 99%
“…Overall, whole-genome sequencing projects and the rise of bioinformatics have triggered the birth of a new era of vaccine research and development, leading to a new generation of vaccines designed by deciphering the information provided by genome sequences and using it to better understand the host–pathogen interactions [ 46 ]. Riding on the capacity developed, as well as the gains from the use of bioinformatics to develop insights into the dynamics of other infectious diseases, means that South African scientists are poised to continue applying -omics informatics approaches to advance the prevention and treatment of diseases, including COVID-19 [ 46 , 47 ].…”
Section: Bioinformatics Approaches To Optimize Research and Developmentmentioning
confidence: 99%